Need Assessment For Sex Educational Amongst The School Children - Thakor H.G; Kumar P (Wolters Kluwer Medknow Publications, 1998)
Research question: Will the sex education given to the students help in STD prevention, population control and in their future sex life. Hypothesis : In order to have a successful school based sex education programme, it is necessary to involve the students at every stage of decision making. Objectives: (!) To assess the perceived need of the students of both sexes about sex education. (2) To decide about age to start with, agencies to be involved, contents to be covered during such programme. (3) To compare the responses between two sexes and to identify the areas of intervention. Study design: Cross- sectional interview based on structured questionnaire. Settings: Two private higher secondary schools (one each for boys and girls) of Surat city participants: 189 students(108 boys and 81 girls) of 11th and 12 the standards Statistical analysis: Chi square test and standard error of the difference between means(z test). Results: Need of sex education is universal as out of 189 students, 97 percent of them agreed to it. The preferred age to start the sex education was lower by 2 years in girls (14.6 years) than boys. Doctors or health workers were the preferred choice for giving the education, however, in their absence; regular school teachers were next choice. Knowledge about the STDs and their prevention was very poor in both the sexes. Condom was largely appreciated as a means of contraception and its role in preventing the STDs was not known to many student. The awareness was largely confined to AIDS. The knowledge about the time of conception was very poor even in these adolescent girls. The poor knowledge about the various methods of contraception and the prevalent myths about various sexual behaviours such as masturbation were the areas identified for intervention